2010
DOI: 10.1111/j.1365-2699.2010.02270.x
|View full text |Cite
|
Sign up to set email alerts
|

Darwin’s Galapagos gourd: providing new insights 175 years after his visit

Abstract: DarwinÕs contributions to the field of biogeography, stressing the importance of his natural history specimens. Here, we illustrate how a plant collected by Darwin during his visit to Floreana and not collected since can provide insights into dispersal to oceanic islands as well as extinction of island plants, based on ancient DNA from DarwinÕs herbarium specimen.Keywords Cucurbitaceae, DarwinÕs herbarium, extinction, Galapagos, island biogeography, molecular clock, phylogenetics, plant viruses, Sicyos.During … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…However, evidence from other fields and impromptu experimentation at the NHM has demonstrated that DNA can be obtained from a variety of dead plant materials, including preserved nests. The extraction of 'ancient' DNA has become routine in the study of sub-fossil plant material, archaeological sites and herbarium collections (Russo et al, 2008;Lister et al, 2010;Sebastian et al, 2010;Palmer et al, 2012). Attachment materials used to secure a nest to its site are often absent for both suspended and supported nests, but communication materials (camouflage/advertisement) can be examined in museum nests to illustrate and examine variation in use of materials with signal function.…”
Section: Functionmentioning
confidence: 99%
“…However, evidence from other fields and impromptu experimentation at the NHM has demonstrated that DNA can be obtained from a variety of dead plant materials, including preserved nests. The extraction of 'ancient' DNA has become routine in the study of sub-fossil plant material, archaeological sites and herbarium collections (Russo et al, 2008;Lister et al, 2010;Sebastian et al, 2010;Palmer et al, 2012). Attachment materials used to secure a nest to its site are often absent for both suspended and supported nests, but communication materials (camouflage/advertisement) can be examined in museum nests to illustrate and examine variation in use of materials with signal function.…”
Section: Functionmentioning
confidence: 99%
“…With the advent of the polymerase chain reaction (PCR), historical museum specimens have been included in phylogenetic or population genetic work and this has allowed the investigation of important topics such as the placement of extinct species in phylogenies (e.g. Wallander & Albert, ; Sebastian, Schaefer & Renner, ), the reconstruction of historic intercontinental movements of crops and their associated pests (Ames & Spooner, ; Schaefer & Renner, ; Yoshida et al ., ), and the origin of herbicide resistance alleles in weeds (Délye, Deulvot & Chauvel, ). The main problem with using museum specimens for these purposes is the low quality of DNAs that can be extracted, especially from poorly preserved samples that were collected several decades or centuries ago (Wandeler, Hoeck & Keller, ).…”
Section: Introductionmentioning
confidence: 99%
“…Among them is Sicyos , the focal clade of this study. Sicyos is a genus in the Cucurbitaceae that has 14 endemic species on the Hawaiian Islands (Wagner & Shannon, 1999), two species on the Galápagos Islands (Sebastian et al. , 2010a), two in Australia, one in New Zealand, and between 41 and 56 species in the Americas, depending on the taxonomic concept applied: several small genera have been included in Sicyos or segregated from it based mostly on fruit characters.…”
Section: Introductionmentioning
confidence: 99%